Dos fundamentos à prática de um ensino histórico-crítico de filosofia - Turini, Mateus Henrique (2020)
This dissertation presents a qualitative analysis about the theoretical-methodological foundations of the teaching of Philosophy in the Basic Education and from Historical-Critical Pedagogy (PHC). To this end, performs a scientific research, with theoretical foundation in the materialism historical-dialectic, in a state school localized in an inland municipality of the state of São Paulo. Starting from the state of the art over the teaching of philosophy, of a brief historic as a curricular component in brazilian school education, of the dialectical analysis in of normative documents discourse and the theoretical-methodological review about the PHC, it was possible to elaborate a proposal of historical-critical teaching Philosophy for High School. This contribution is expressed through a didactic method and an educational game, called Philosophical Deck. After repeated applications, it is possible to affirm that the game was able to fulfill with expected role for this research: the in of to be a pedagogical activity that enables the live of the cathartic moment inside in the school times and spaces.